Incorporating coastal blue carbon into subnational greenhouse gas inventories - Zhao, Peng; Ge, Song; He, Dinghua; Zhong, Cairong; Wang, Boyan; Wang, Xiaokang; Wang, Fengxia; Kao, Shuhji (Frontiers in Marine Science, 2022)
The climate mitigation potential of coastal blue carbon including mangroves, seagrasses and tidal marshes have been widely recognized, and guidelines for incorporating coastal wetlands into greenhouse gas inventories released by IPCC in 2014 make it possible to bring coastal blue carbon into multilevel climate governance regimes. However, the intricate guidelines and inadequate data block governments from accounting and reporting their coastal blue carbon in inventories. In this research, we integrated and simplified the equations and assumptions of IPCC inventory guidance on coastal wetlands, and took Hainan province of China as a case study by (1) formulating a land use change matrix from high resolution satellite imagery for the years of 2010 to 2020, (2) compiling dataset of emission factors for coastal wetlands of Hainan, and (3) estimating CO2, CH4, and N2O emissions from coastal wetlands in Hainan. We reveal that the mangroves’ area increased from 4,190.7 ha in 2010 to 4,644.1 ha in 2020, with a net increase of 483.9 ha from tidal flats and aquaculture ponds. The weighted average EFAGB and EFsoil of Hainan is 61.7 MgC ha-1 and 227.4 MgC ha-1, respectively,estimated from peer-reviewed literature in both Chinese and English. The annual average net CO2 emission of mangroves of Hainan is -26974.3 MgCO2e yr-1. CO2 emission from mangrove deforestation and N2O emission from shrimp aquaculture in coastal aeras may offset the efforts of coastal wetlands conservation and restoration. Countries and sub-country regions are encouraged to bring coastal blue carbon into greenhouse gases inventories as soon as possible, and to take a bottom-up strategy to initiate the task at a local level.